ChemInform Abstract: Synthesis of 2‐Substituted Benzothiazoles from 1‐Iodo‐2‐nitrobenzenes by a Copper‐Catalyzed One‐Pot Three‐Component Reaction. Issue 30 (4th July 2013) - Liu, Jidan; Gui, Qingwen; Yang, Zhiyong; Tan, Ze; Guo, Ruqing; Shi, Ji‐Cheng
Abstract A broad spectrum of 2‐substituted benzothiazoles is available in the presence of sodium sulfide, where a wide range of functional groups is tolerated at the arene moieties of the substrates.